Analisis Etika Jual Beli dalam Transaksi Shopee: “Perbandingan Sistem Pembayaran COD (Cash on Delivery) dan ShopeePay dalam Perspektif Hukum Ekonomi Islam”: Analysis of the Ethics of Selling and Buying in Shopee Transactions: "Comparison of COD (Cash on Delivery) and ShopeePay Payment Systems in the Perspective of Islamic Economic Law” - Wardatul Umniyah; Faizul Abrori; Budi Sufyanto; Mustaqim Makki (Al-Kharaj: Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2025)
This research aims to analyze the comparison of the Cash on Delivery (COD) and ShopeePay payment systems in buying and selling transactions through the Shopee platform based on the perspective of Islamic economic law. This research uses a qualitative method with a descriptive approach. Data collection techniques were carried out through literature studies, interviews with Shopee consumers, observation of the transaction process, and documentation. The results showed that the COD system provides benefits in the form of easy return of goods, but creates inconvenience due to additional service fees that are not transparent. In contrast, the ShopeePay system is considered more efficient, transparent, and in accordance with the principles of justice in Islam because the costs are clear at the beginning and facilitate the process of delivering goods. The conclusion of this study is that both payment methods are allowed in Islam as long as they fulfill the principles of justice, clarity of contract, and do not contain elements of gharar, usury, and injustice. The researcher suggests that e-commerce players convey clear cost information to consumers from the start. The implication of this research is the importance of applying Islamic business ethics in digital transactions to create fair, transparent, and responsible transactions for all parties involved